Night Admission at a Psychosocial Care Center III - Thuany Cristine Santos da Silva; Tatiana Marques dos Santos; Izabella de Góes Maciel Tavares Campelo; Maria Manuela Vila Nova Cardoso; Adriana Dias Silva; Maria Angélica de Almeida Peres (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to analyze night admission characteristics at a Psychosocial Care Center III (CAPS III - Centro de Atenção Psicossocial). Method: a qualitative research, whose data were collected with 15 nursing professionals from November to April 2016, through a semi-structured interview. Results: it was verified that night admission is provided by the nursing team in different dynamics from the day care. This team has strategies of care during crisis, avoiding search for other network services and maintaining the CAPS in its function within the psychosocial model. Final considerations: service operation depends on the nursing team for its permanence condition in all shifts, which leads to the need to think about the legislation reformulation that structures the CAPS III team, in order to guarantee the interdisciplinary care provided by the Brazilian Psychiatric Reform in this device, which should replace hospitalization in a specialized institution.